Amazing Magic Tricks: To Confound and Astound - Stone, Chris (London Collins & Brown, 2019)
The world's greatest and most celebrated magicians, conjurers and illusionists can make us believe the unbelievable, the impossible possible. But, of course, just like everybody else these conjurors had to start at a beginning. They too had to learn simple (but effective) card tricks, easy (but imaginative) coin tricks and basic (but still mind boggling) sleight-of-hand tricks before advancing to more innovative and radical skills and techniques.Amazing Magic Tricks is a cool compendium of diverse tricks to inspire all aspiring magicians to pick up a wand and impress their friends and family! Full of trivia as well as simple illusions to practice, perfect and perform at home, Amazing Magic Tricks will guide you on your way to becoming a master magician quicker than you can say 'Ta-Dah!'.
Keywords: Magic and Trick